2010
DOI: 10.1002/pd.2587
|View full text |Cite
|
Sign up to set email alerts
|

HCMV seroprevalence and associated risk factors in pregnant women, Havana City, 2007 to 2008

Abstract: Although pregnant women in Cuba have high seroprevalence rates for HCMV, those younger than 20 years and nulligravidae are at risk of acquiring infection during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
4
14
1
2
Order By: Relevance
“…The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23]. …”
Section: Discussionmentioning
confidence: 99%
“…The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this could be due to an epidemiological coincidence of infections with diverse viruses. This hypothesis deserves further testing in Cuban population where a high seroprevalence of herpesviruses (CMV, herpes simplex type 1 virus (HSV) and Epstein Barr virus(EBV) infection has been previously described [30-32,56] . …”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of debate concerning maternal age and CMV infection; while many investigators observed that, elder women were at higher risk of CMV infection [28], others reported the reverse [31]. However, Bukbuk et al, documented that, increasing maternal age was significantly associated with rubella infection among Nigerian women [32].…”
Section: Discussionmentioning
confidence: 99%